Parametric study of deteriorating precast concrete double-tee girder bridges using computational models. (1st March 2021) - Seo, Junwon; Kidd, Brian
Highlights: 3D computational models for two tested double-tee bridges were created. The models were calibrated with the testing data to replicate actual live load distribution factors. A parametric study with variation in double-tee bridge parameters was conducted. The effects of different bridge parameters on live load distribution factors were explored. The span length was found to be a significant parameter on live load distribution factors. Abstract: This paper aims to study the effects of different parameters of precast concrete double-tee (DT) girder bridges on the live-load distribution factors (LLDFs) using 3D computational models. The models were created for two DT girder bridges (including 584 mm deep and 762 mm deep bridges) tested with a rating truck using solid and shell elements in CSi Bridge. From the field tests, LLDFs were initially calculated. The models were calibrated with the field LLDFs and then different parameters, encompassing span length, concrete strength, deck width, diaphragm usage, and width to length ratio, were adjusted individually to explore the variation in LLDFs. Each of the parameters was investigated in this study for DT girder bridges. The AASHTO LRFD interior LLDFs were generally accurate for the DT girder bridges with significant joint damage. It was demonstrated that the deck width, concrete strength, and diaphragm location had very little influence on the LLDFs, whereas the span length and width to length ratio had significantly affected the LLDFs. Strictly speaking, the exterior and interior LLDFs decreased as the span length increased. The pattern for the interior LLDFs is only in agreement with the AASHTO LRFD specifications, while the pattern for the exterior LLDFs is not consistent with the AASHTO LRFD LLDFs calculated using the lever rule without consideration of span length. As a final point, as the width to length ratio increased, the LLDFs increased.